The Appreciation and Study of Qur’an Manuscripts from Southeast Asia: Past, Present, and Future - Gallop, Annabel Teh (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
The focus of this paper is not on theological aspects of the Qur’an, or on the study of the Qur’anic sciences in Southeast Asia over the past centuries, but rather to attempt to trace the path of the appreciation of old copies of the Qur’an  in  Southeast  Asia  as  part  of  the  historical  record  of  the  Islamic heritage  of  the  region.   In  this  light,  Qur’an  manuscripts  are  viewed  as objects  of  material  culture  which  can  cast  light  on  the  societies  which produced  them,  and  as  works  of  art  which  testify  to  the  heights  of  artistic creativity  in  the  region,  for  illuminated  Qur’an  manuscripts  represent  the pinnacle  of  achievements  in  the  arts  of  the  book  in  Southeast  Asia.  Thishistorical record can be measured through a survey of how, where, when and by whom Qur’an manuscripts in Southeast Asia were collected, documented, studied and published, both in Southeast Asia itself and in the west.